Hepatocyte-Specific Hepatocyte Nuclear Factor 4 Alpha (HNF4α) Deletion Decreases Resting Energy Expenditure by Disrupting Lipid and Carbohydrate Homeostasis - Huck, Ian (Gene Expr, 2021)
Hepatocyte nuclear factor 4 alpha (HNF4α) is required for hepatocyte differentiation and regulates expression of genes involved in lipid and carbohydrate metabolism including those that control VLDL secretion and gluconeogenesis. Whereas previous studies have focused on specific genes regulated by HNF4α in metabolism, its overall role in whole-body energy utilization has not been studied. In this study, we used indirect calorimetry to determine the effect of hepatocyte-specific HNF4α deletion (HNF4α-KO) in mice on whole-body energy expenditure (EE) and substrate utilization in fed, fasted, and high-fat diet (HFD) conditions. HNF4α-KO had reduced resting EE during fed conditions and higher rates of carbohydrate oxidation with fasting. HNF4α-KO mice exhibited decreased body mass caused by fat mass depletion despite no change in energy intake and evidence of positive energy balance. HNF4α-KO mice were able to upregulate lipid oxidation during HFD, suggesting that their metabolic flexibility was intact. However, only hepatocyte-specific HNF4α-KO mice exhibited significant reduction in basal metabolic rate and spontaneous activity during HFD. Consistent with previous studies, hepatic gene expression in HNF4α-KO supports decreased gluconeogenesis and decreased VLDL export and hepatic β-oxidation in HNF4α-KO livers across all feeding conditions. Together, our data suggest that deletion of hepatic HNF4α increases dependence on dietary carbohydrates and endogenous lipids for energy during fed and fasted conditions by inhibiting hepatic gluconeogenesis, hepatic lipid export, and intestinal lipid absorption resulting in decreased whole-body energy expenditure. These data clarify the role of hepatic HNF4α on systemic metabolism and energy homeostasis.